Positive Almost Periodic Solutions for a Time-Varying Fishing Model with Delay - Xia Li; Yongkun Li; Chunyan He (International Journal of Differential Equations)
This paper is concerned with a time-varying fishing model with delay. By means of the continuation theorem of coincidence degree theory, we prove that it has at least one positive almost periodic solution.